Chemical dry cleaning technology for reliable 65 nm CMOS contact to NiSi/sub x - Honda, M.; Tsutsumi, K.; Harakawa, H.; Nomachi, A.; Murakami, K.; Ooya, K.; Kudou, T.; Nagamatsu, T.; Ezawa, H. (Proceedings of the IEEE 2005 International Interconnect Technology Conference, 2005, 2005)
Nickel silicide (NiSi/sub x/) is being considered as a replacement for the currently used silicides. A native oxide film on the nickel silicide surface causes high contact resistance. The cleaning technology for removal of the oxide film on NiSi/sub x/ is a critical issue for 65 nm generation CMOS devices. The effect of a chemical dry treatment prior to contact metallization was studied. It was confirmed that the chemical dry treatment is effective for obtaining low stable contact resistance, and is a key technology for the high yield manufacture of CMOS devices.